Tanzania : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report, 2003)
This paper presents the Second Progress Report 2001/02 for Tanzania's Poverty Reduction Strategy. The report highlights the mileage achieved during 2001/02, and provides a synthesized poverty profile. It presents information on macroeconomic policies and structural reforms and how they link to poverty reduction. Issues of private sector development, impact of globalization, and debt sustainability are also part of the report. The report also discusses the implementation status of the key priority sectors for poverty reduction and the status of the Local Government Reform program.